Long-term care status for the elderly with different levels of physical ability: a cross-sectional survey in first-tier cities of China - Mingchao Zhou; Fubing Zha; Fang Liu; Jing Zhou; Xiangxiang Liu; Jiehui Li; Qingqing Yang; Zeyu Zhang; Feng Xiong; Dianrui Hou; Hongyun Weng; Yulong Wang (BMC, 2023)
Abstract Background Long term care (LTC) services for functionally impaired senior citizens are crucial for addressing the challenges of aging. However, research on eligibility criteria and coverage of LTC in China is lacking. Our objective is to assess the current status of LTC and explore eligibility criteria and coverage for the elderly. Methods This is a cross-sectional study conducted in two first-tier cities in China. Residents aged 65 or over were recruited from a nursing home and four primary hospitals. Participants were divided into three groups (bedridden, domestic, and community), then six grades (grade one to six) according to the Longshi Scale, and their functional ability was assessed using the Modified Barthel Index. Information such as diseases, complications, and daily care needs were collected. Nursing staff were invited to indicate patients' needs for care. A one-way ANOVA test, Kruskal Wallis H test and Mann-Whitney U test were used to explore the differences of variables in three Longshi groups or Longshi grades. Results Among all 1157 participants, with an average age of 80.54, 69.3% were in the bedridden group. The most common diagnosis was stroke (71.4%), with the most prevalent complication being pulmonary infection (25.2%). In the nursing assessment, basic health care, disease care, activity care, complication prevention care and psychosocial care were summarized as the five main aspects of LTC for the elderly. Feeding, bathing, drinking, bowel management and bladder management were identified as the basic care which fulfills participants' basic physical needs in each Longshi group. Mouth care, artificial airway management, and body reposition, which can prevent immobility complications, were highly demanded by bedridden elderly. Conclusions The elderly in grade one to three are the ones in need of LTC most. The content of LTC for elderly should include basic care which fulfills their basic physical needs and complication care which can prevent immobility complications. The evidence of this research may contribute to the design of LTC in China. Trial registration The study design was registered in the Chinese Clinical Trial Registry (ChiCTR-2000034067, Registered 22 Jun 2020, http://www.chictr.org.cn/showproj.aspx?proj=54770 ).